Comparative Cost Analysis of Domestic Container Shipping Network: A Case Study of Indonesian Sea-Toll Concept - Wegit Triantoro (Jurnal Penelitian Transportasi Laut, 2020)
The Logistics Performance Index (LPI) of Indonesia shows minor improvement compared to neighbouring countries such as Singapore and Malaysia. The economic disparity between Indonesia’s eastern and western regions has reportedly become one of the fundamental problems in the country. Consequently, an ambitious project on shipping connectivity improvement, namely the ‘Sea-Toll’, has been proclaimed by the Indonesian government to overcome this chronic problem. One of the most influential parameters for measuring the success rate of this project is cost efficiency. Therefore, this paper proposes a comparative approach by constructing a generalised cost model. It develops a measurement for transport costs that combines actual freight cost with the value of time attached to delivery activities concerning cargo types. Overall results study depend on the shipping network is described in terms of a current and future condition. This condition is because the factor of economies of scale has a significant influence in the combination of actual empirical data and extractions of regression approach with the function of vessel size. Finally, all scenarios show that there is a positive relationship with a convincing impact on efforts to save costs for domestic shipping routes after the implementation of the sea-Toll program.